ANALYSIS OF THE SLANG WORD 'KUY' IN EVERYDAY LANGUAGE CONTEXT - Suci Rahmadani; Jamaluddin Nasution; Widya Karolina Br Pardede; Alyah Putri Nabilla; Kesya Klarissya Br Pandia (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study analyzes the use of the slang word â€œkuyâ€ in the daily language of Indonesian society, particularly among teenagers and young adults. Using a qualitative approach and descriptive-analytical method, data were collected through questionnaires from 107 respondents, in-depth interviews, social media observation, and digital documentation. The findings show that â€œkuyâ€ originates from the phonological reversal of the word â€œyukâ€ in prokem language, which emerged in the 1980s and gained popularity on social media around 2014. Semantically, 89.7% of respondents understand â€œkuyâ€ as an invitation, but pragmatically, it also serves as a symbol of social closeness and group identity, with 57.9% considering it important to express familiarity among peers. The word is most commonly used to invite someone to do something (52.8%) and appears more frequently in social media communication than in face-to-face interaction. Its usage is moderate, with 85% of respondents using it occasionally, reflecting the younger generationâ€™s ability to code-switch according to the communication context. This study concludes that â€œkuyâ€ is not only a linguistic expression but also a cultural artifact that reflects the creativity and social dynamics of Indonesiaâ€™s urban digital generation.Â Keywords: slang, kuy, sociolinguistics, prokem language, social media, adolescent identity, language variation, digital communication, Gen Z, Indonesian slang.Â Abstrak: Studi ini menganalisis penggunaan kata slang "kuy" dalam bahasa sehari-hari masyarakat Indonesia, khususnya di kalangan remaja dan dewasa muda. Dengan menggunakan pendekatan kualitatif dan metode deskriptif-analitis, data dikumpulkan melalui kuesioner dari 107 responden, wawancara mendalam, observasi media sosial, dan dokumentasi digital. Temuan menunjukkan bahwa "kuy" berasal dari pembalikan fonologis kata "yuk" dalam bahasa prokem, yang muncul pada 1980-an dan mendapatkan popularitas di media sosial sekitar tahun 2014. Secara semantik, 89,7% responden memahami "kuy" sebagai undangan, tetapi secara pragmatis, itu juga berfungsi sebagai simbol kedekatan sosial dan identitas kelompok, dengan 57,9% menganggapnya penting untuk mengekspresikan keakraban di antara teman sebaya. Kata itu paling umum digunakan untuk mengundang seseorang untuk melakukan sesuatu (52,8%) dan muncul lebih sering dalam komunikasi media sosial daripada dalam interaksi tatap muka. Penggunaannya tergolong moderat, dengan 85% responden menggunakannya sesekali, mencerminkan kemampuan generasi muda untuk beralih kode sesuai konteks komunikasi. Studi ini menyimpulkan bahwa "kuy" bukan hanya sebuah ekspresi linguistik, tetapi juga artefak budaya yang mencerminkan kreativitas dan dinamika sosial generasi digital urban Indonesia.Â Kata kunci: bahasa gaul, kuy, sosiolinguistik, bahasa prokem, media sosial, identitas remaja, variasi bahasa, komunikasi digital, Gen Z, bahasa gaul Indonesia.